2019
DOI: 10.1039/c9cy01502g
|View full text |Cite
|
Sign up to set email alerts
|

Manganese PNP-pincer catalyzed isomerization of allylic/homo-allylic alcohols to ketones – activity, selectivity, efficiency

Abstract: Manganese PNP pincer complexes are excellent catalysts for the isomerization of allylic alcohols to the ketones. The reaction proceeds via a dehydrogenation/hydrogenation mechanism as shown by DFT calculations and deuterium labelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Under the reaction conditions, aliphatic as well as cyclic ketones were also well tolerated (62−73%) (59 and 60). Interestingly, the reaction proceeded smoothly with a heteroatom-containing acetophenone derivative in moderate yield (76%) (61). The reaction of acetophenone and 4-iodoacetophenone with 3-aminopropan-1-ol also afforded the expected products in moderate yields (62 and 63).…”
Section: Scheme 3 Synthesis Of Bioactive Natural Product (±)-Angustur...mentioning
confidence: 95%
See 1 more Smart Citation
“…Under the reaction conditions, aliphatic as well as cyclic ketones were also well tolerated (62−73%) (59 and 60). Interestingly, the reaction proceeded smoothly with a heteroatom-containing acetophenone derivative in moderate yield (76%) (61). The reaction of acetophenone and 4-iodoacetophenone with 3-aminopropan-1-ol also afforded the expected products in moderate yields (62 and 63).…”
Section: Scheme 3 Synthesis Of Bioactive Natural Product (±)-Angustur...mentioning
confidence: 95%
“…The relative Gibbs free energies of all the states were calculated using the LANL2DZ basis set for Mn and 6-31G** basis set for nonmetal elements. The base-mediated activation of the precatalyst Mn1 generated the intermediate II . Then 2-aminobenzyl alcohol was activated via a metal–ligand cooperative pathway where the proton was transferred to the imido-N in the ligand backbone followed by the formation of Mn-alkoxy species III (Δ G = 1.66 kcal/mol) .…”
Section: Mechanistic Insightmentioning
confidence: 99%
“…Isomerization of 7b into 7a represents a rare example of a Mn-catalyzed allylic alcohol isomerization reaction . Typically, isomerization of allylic alcohols requires a precious-metal catalyst .…”
mentioning
confidence: 99%
“…Typically, isomerization of allylic alcohols requires a precious-metal catalyst . Nickel, molybdenum, iron, and cobalt have been utilized, , and only one manganese catalyst has been reported . The allylic alcohol isomerization capability of the HL Ph Mn­(CO) 3 Br and base system in toluene was tested for the three different allyl alcohols 7b , 10b , and 11b and gave quantitative conversion (Scheme ).…”
mentioning
confidence: 99%
“…The only report on the manganese-catalyzed isomerization of allylic and homoallylic alcohols to the corresponding carbonyl product was disclosed by Vries (Scheme 84). 419 Ph MACHO–Mn( i )-complex Mn39 catalyzed the reaction in the presence of a catalytic amount of KO t Bu at 120 °C. The detailed DFT study revealed the involvement of the dehydrogenation/hydrogenation sequence, which was further verified by the isolation of the α,β-unsaturated ketone intermediate and a deuterium labeling experiment (Scheme 85).…”
Section: Borrowing Hydrogen/hydrogen Auto-transfermentioning
confidence: 99%